Role of Product Quality and Store Atmosphere on Purchase Decision of Clothing Product Vintage Vibes - Siti Aisyah; Chairul Anwar; Nugroho Djati Satmoko; Sutrisno; Uli Wildan Nuryanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The objectives of this study is to examine role of product quality and store atmosphere on purchase decision of clothing product of Vintage Vibes. This research uses quantitative research. This study aims to analyze the influence of product quality and store atmosphere on purchasing decisions at Vintage Vibes. In this study, there are two kinds of variables, namely the independent variable and the dependent variable. The independent variables in this study are product quality and the atmosphere in the store, while the dependent variable is purchasing decisions. The unit of analysis in this study is